The Essentials of Financial Policies and Interest Rate Shocks in Downturn and Upswing of Stock Market: A Cointegration and Causality Analysis - Bhutto, Sarfaraz Ahmed; Rajper, Zulfiqar Ali; Kishan, Jai (International Journal of Psychosocial Rehabilitation, 2020)
The financial market (stock market) of any country play pivotal role in measuring economic prosperity of country, and it is notion that the global financial crisis has essentially destroyed all the stock exchanges. Therefore, the current study focuses on finding factors related to financial policies that affect stock market upswing and downturn. The interest rates and other linked monetary policies determine the direction of the stock market. Study considered monthly data from the period of Jan-2005 to Dec-2018 and measured the correlation, Cointegration and causality among variables. The GARCH (1, 1) model is used to generate stock market index variation and interest rate shocks. The developed model analyzes by using trace rank test of Johansen Cointegration analysis, Granger causality analysis and Impulse response analysis with proper contemplation of all diagnostic test. The results confirm the long-run negative and significant relationship of interest rate shocks, inflation rate, financial crisis, and stock market volatility. In a long-run, the exchange rate and money supply observed positively with stock market. All predictors and outcome variables have a causal relation with each other, but the financial crisis of the world does not show as causal relation with the stock exchange volatility. This study will help policymakers to take a closer look at these factors when making monetary and all associated policies because the study provides a realistic picture before the crisis, during the crisis and after the crisis effects of all these factors on the stock market. Moreover, it is imperative for authorities to look at all the factors that affect the market deeply.